SARS‐CoV‐2 RNA detection in stool samples from acute gastroenteritis cases, Brazil - Fumian, Tulio M. (J Med Virol, 2021)
We described the detection of severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) in stool samples from patients presenting only acute gastroenteritis (AGE) symptoms. From January to July 2020, 121 AGE stool samples were screened by quantitative reverse‐transcription polymerase chain reaction. We detected SARS‐CoV‐2 in 27.5% of samples received during the epidemic period. No infectious viruses were observed in Vero E6 cells.